Analysis of preliminary phytochemical screening of Typhonium flagelliforme - Galehpardsari, Motahareh Nobakht; Abdul Kadir, Mihdzar; Stanslas, Johnson (Academic Journals, 2010)
Typhonium flagelliforme (Araceae) is a medicinal herb which is endowed with curative properties against a variety of illness including injuries, oedema, coughs, pulmonary ailments, bleeding and cancer. In order to assess its phytochemical components, an experiment was conducted on one to six month old ex vitro and in vitro extracts of T. flagelliforme. The active (ex vitro and in vitro) extracts of T. flagelliforme were screened for phytochemicals components such as alkaloids, flavonlids, terpenoids and steroids. Alkaloids and flavonoids are the main phytochemical constituents of T. flagelliforme which are found to be in the highest amount in two and four month old of ex vitro plants. High amounts of main phytochemical constituents were observed during the flowering process which started in two month old plant and finished at the end of the three month old plant.